2015
DOI: 10.1158/1078-0432.ccr-14-2728
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of ER Signaling as an Adaptive Mechanism of Cell Survival in HER2-Positive Breast Tumors Treated with Anti-HER2 Therapy

Abstract: Purpose To investigate the direct effect and therapeutic consequences of epidermal growth factor receptor 2 (HER2)-targeting therapy on expression of estrogen receptor (ER) and Bcl2 in preclinical models and clinical tumor samples. Experimental design Archived xenograft tumors from two preclinical models (UACC812 and MCF7/HER2-18) treated with ER and HER2-targeting therapies, and also HER2+ clinical breast cancer specimens collected in a lapatinib neoadjuvant trial (baseline and week 2 post treatment), were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 37 publications
4
88
0
1
Order By: Relevance
“…Crosstalk between ER and the EGFR/HER2 pathway plays a major role in endocrine resistance [44]. Moreover, increased ER signaling in patients with HER2+/ER + tumors treated with lapatinib alone has been reported, suggesting that this event may involve the activation of FoxO3A, as a result of PI3K/Akt inhibition [45,46]. Importantly, this lapatinib-induced up-regulation of ER is accompanied by parallel up-regulation of the anti-apoptotic protein Bcl-2, potentially leading to cell survival and lapatinib resistance [45,46].…”
Section: Estrogen Receptor Pathwaymentioning
confidence: 99%
“…Crosstalk between ER and the EGFR/HER2 pathway plays a major role in endocrine resistance [44]. Moreover, increased ER signaling in patients with HER2+/ER + tumors treated with lapatinib alone has been reported, suggesting that this event may involve the activation of FoxO3A, as a result of PI3K/Akt inhibition [45,46]. Importantly, this lapatinib-induced up-regulation of ER is accompanied by parallel up-regulation of the anti-apoptotic protein Bcl-2, potentially leading to cell survival and lapatinib resistance [45,46].…”
Section: Estrogen Receptor Pathwaymentioning
confidence: 99%
“…Previous studies had shown a greater benefit of lapatinib in patients with HER2-positive tumors that are ER and PR negative, compared with HR-positive patients [26]. Further, the multiple levels of cross talk between ER and HER2 have indicated that antiestrogen agents could induce EGFR and HER2 expression through the positive regulatory loop within cell lines, and PI3K kinase mediate HER2 overexpression providing an escape resistance to trastuzumab [27,28]. This mechanism contributes to de novo and acquired resistance in anti-HER2 therapies; the dual kinase inhibitor lapatinib could disrupt regulatory loop and restore the sensitivity of HR [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the multiple levels of cross talk between ER and HER2 have indicated that antiestrogen agents could induce EGFR and HER2 expression through the positive regulatory loop within cell lines, and PI3K kinase mediate HER2 overexpression providing an escape resistance to trastuzumab [27,28]. This mechanism contributes to de novo and acquired resistance in anti-HER2 therapies; the dual kinase inhibitor lapatinib could disrupt regulatory loop and restore the sensitivity of HR [27,28,29]. The data from this study suggest that p95HER2 might activate the progression and aggressiveness of HR-positive tumors in HER2+ patients, and lapatinib could suppress the growth of HR-positive tumors by inhibiting intracellular HER2 molecule locating upstream of the PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is of key importance to be able to identify such tumors in order to properly select those patients who might be treated with anti-HER2 therapies exclusively, therefore avoiding the toxicity related to CT [79]. In this context, the mentioned crosstalk between the HER2 and ER pathways that may favor acquired resistance to anti-HER2 treatment must be particularly considered [80,81]. The PAMELA and TBRC006 trials combined double anti-HER2 blockade with trastuzumab and lapatinib plus ET therapy in the case of HR+ patients.…”
Section: Her2-positive Breast Cancermentioning
confidence: 99%